Gestión en los servicios de tránsito de contenedores en el puerto del Callao y su influencia en la competitividad de las empresas exportadoras e importadoras - Castillo Torbalay, Yahir Gean Marco (2018)
This paper intends to demonstrate how is the management of container services in the port of Callao, how the whole chain develops and how it influences each process, we decided to carry out this research since we are directly involved in the operational work, and That in our work center we face this problem daily, each of the members of this group is immersed in this problem so we decided to do a thorough investigation, why this chaotic situation, bureaucracy, processes, delay and Especially as the exporters or importers are affected, often costs are the main problem, the ports of exit (DP WORLD, APM TERMINALS) always present congestion, bureaucratic obstacles and often present security problems within their own facilities, problem That many times one does not know that they do not usually inform the public involved in this field. For the same problem it was decided to investigate optimal solutions that improve the logistics chain, so that all those involved are benefited and above all, as professionals, provide assistance tools that allow the development of foreign trade.